A 12‐week DBPC dose‐finding study with sublingual monomeric allergoid tablets in house dust mite‐allergic patients. Issue 1 (10th May 2016) - Hüser, C.; Dieterich, P.; Singh, J.; Shah‐Hosseini, K.; Allekotte, S.; Lehmacher, W.; Compalati, E.; Mösges, R.
Abstract: Background: In sublingual immunotherapy, optimal doses are a key factor for therapeutic outcomes. The aim of this study with tablets containing carbamylated monomeric house dust mite allergoids was to determine the most effective and safe dose. Methods: In this double‐blind, placebo‐controlled dose‐finding study, 131 patients with house dust mite‐induced allergic rhinoconjunctivitis were randomized to 12‐week treatments with 300 UA/day, 1000 UA/day, 2000 UA/day, 3000 UA/day or placebo. Conjunctival provocation tests (CPT) were performed before, during and after treatment. The change in mean allergic severity (primary endpoint), calculated from the severity of the CPT reaction, and the proportion of patients with an improved CPT threshold (secondary endpoint) determined the treatment effect. Results: The mean allergic severity decreased in all groups, including the placebo group. It was lower in all active treatment groups (300 UA/day: 0.14, 1000 UA/day: 0.15, 2000 UA/day: 0.10, 3000 UA/day: 0.15) than in the placebo group (0.30). However, this difference was not statistically significant ( P < 0.1). The percentage of patients with an improved CPT threshold was higher in the active treatment groups (300 UA/day: 73.9%; 1000 UA/day: 76.0%; 2000 UA/day: 88.5%; 3000 UA/day: 76.0%) than in the placebo group (64.3%). The difference between placebo and 2000 UA/day was statistically significant ( P = 0.04). In 13 (10%) exposed patients, a total of 20 treatment‐related adverse events of mild severity were observed. Conclusions: The 12‐week daily treatment using 2000 UA/day monomeric allergoid sublingual tablets is well tolerated and reduces the CPT reaction in house dust mite‐allergic patients.